Corporate Governance: An Assessment. - Becht, M; Jenkinson, T; Mayer, C (OUP, 2005)
Corporate governance is one of the most topical and controversial areas of business and finance. This article provides an overview of the questions that it raises and proposed policy responses. It points to the diversity in systems of corporate governance around the world, the apparently paradoxical performance of different systems and an association with different forms of corporate-governance failures. The article discusses a range of proposed remedies including the restructuring of boards, regulation of markets in corporate control and limitations on executive remuneration. It also considers whether the need for harmonized corporate-governance rules can be diminished by freedom of mobility of corporations and competition between legal systems.